2023
DOI: 10.1115/1.4063000
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Subject-Specific Aortic Hemodynamic Effects of Valvular Lesions in Rheumatic Heart Disease

Abstract: Rheumatic heart disease (RHD) is a neglected tropical disease despite the substantial global health burden. In this study, we aimed to develop a lower cost method of modeling aortic blood flow using subject-specific velocity profiles, aiding our understanding of RHD's consequences on the structure and function of the ascending aorta. Echocardiography and CMR are often used for diagnosis, including valve dysfunction assessments. However, there is a need to further characterize aortic valve lesions to improve tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The second limitation is the assumption of a parabolic-shaped spatial profile for the inlet velocity [44]. A few studies have suggested the importance of using a patient-specific three-dimensional velocity profile at the inlet to accurately describe the blood flow in the aorta [81][82][83]. However, the importance in general becomes less profound as the flow moves downstream due to the accumulated influence of vessel walls.…”
Section: Limitations Of Current Studymentioning
confidence: 99%
“…The second limitation is the assumption of a parabolic-shaped spatial profile for the inlet velocity [44]. A few studies have suggested the importance of using a patient-specific three-dimensional velocity profile at the inlet to accurately describe the blood flow in the aorta [81][82][83]. However, the importance in general becomes less profound as the flow moves downstream due to the accumulated influence of vessel walls.…”
Section: Limitations Of Current Studymentioning
confidence: 99%